Popliteal artery aneurysm resembling popliteal cyst: a case report - Ozgocmen, S; Kocakoc, E; Ardicoglu, O; Kiris, A (Editions Scientifiques Medicales Elsevier, 2001)
[Abstract Not Available]
Keywords: Baker's cyst; popliteal artery aneurysm; ultrasound